Cervical Cancer Screening: A Review - Perkins, Rebecca B; Wentzensen, Nicolas; Guido, Richard S; Schiffman, Mark (JAMA : the journal of the American Medical Association, 2023)
Each year in the US, approximately 100 000 people are treated for cervical precancer, 14 000 people are diagnosed with cervical cancer, and 4000 die of cervical cancer. Essentially all cervical cancers worldwide are caused by persistent infections with one of 13 carcinogenic human papillomavirus (HPV) genotypes: 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, and 68. HPV vaccination at ages 9 through 12 years will likely prevent more than 90% of cervical precancers and cancers. In people with a cervix aged 21 through 65 years, cervical cancer is prevented by screening for and treating cervical precancer, defined as high-grade squamous intraepithelial lesions of the cervix. High-grade lesions can progress to cervical cancer if not treated. Cervicovaginal HPV testing is 90% sensitive for detecting precancer. In the general population, the risk of precancer is less than 0.15% over 5 years following a negative HPV test result. Among people with a positive HPV test result, a combination of HPV genotyping and cervical cytology (Papanicolaou testing) can identify the risk of precancer. For people with current precancer risks of less than 4%, repeat HPV testing is recommended in 1, 3, or 5 years depending on 5-year precancer risk. For people with current precancer risks of 4% through 24%, such as those with low-grade cytology test results (atypical squamous cells of undetermined significance [ASC-US] or low-grade squamous intraepithelial lesion [LSIL]) and a positive HPV test of unknown duration, colposcopy is recommended. For patients with precancer risks of less than 25% (eg, cervical intraepithelial neoplasia grade 1 [CIN1] or histologic LSIL), treatment-related adverse effects, including possible association with preterm labor, can be reduced by repeating colposcopy to monitor for precancer and avoiding excisional treatment. For patients with current precancer risks of 25% through 59% (eg, high-grade cytology results of ASC cannot exclude high-grade lesion [ASC-H] or high-grade squamous intraepithelial lesion [HSIL] with positive HPV test results), management consists of colposcopy with biopsy or excisional treatment. For those with current precancer risks of 60% or more, such as patients with HPV-16-positive HSIL, proceeding directly to excisional treatment is preferred, but performing a colposcopy first to confirm the need for excisional treatment is acceptable. Clinical decision support tools can facilitate correct management. Approximately 100 000 people are treated for cervical precancer each year in the US to prevent cervical cancer. People with a cervix should be screened with HPV testing, and if HPV-positive, genotyping and cytology testing should be performed to assess the risk of cervical precancer and determine the need for colposcopy or treatment. HPV vaccination in adolescence will likely prevent more than 90% of cervical precancers and cancers.